Expanding Meaningfulness: Perceptions and Strategy Use of Chinese International Graduate Students in Disciplinary Reading - Wang, Yang (Journal of International Students, 2019)
This qualitative case study explored two Chinese international graduate students’ beliefs about their reading and reading processes.  The researcher interviewed the participants, asked them to read aloud, analyzed their reading using miscue analysis, and then discussed their reading with them using retrospective miscue analysis (RMA).  The researcher found that readers’ beliefs were not static and text difficulty influenced the students’ reading beliefs and strategy use. Through RMA, both students became aware of their respective reading processes and they both became more confident as readers.  This study suggests that RMA is an effective tool for English-as-an-additional language graduate students, as it helps in the construction of meaning and the improvement of disciplinary literacy skills.